Osteogenic potential of gingival stromal progenitor cells cultured in platelet rich fibrin is predicted by core-binding factor subunit-α1/Sox9 expression ratio (in vitro) - Nugraha, Alexander Patera; Narmada, Ida Bagus; Ernawati, Diah Savitri; Dinaryanti, Aristika; Hendrianto, Eryk; Ihsan, Igo Syaiful; Riawan, Wibi; Rantam, Fedik Abdul (F1000 research, 2018)
Background: Alveolar bone defect regeneration has long been problematic in the field of dentistry. Gingival stromal progenitor cells (GSPCs) offer a promising solution for alveolar bone regeneration. In order to optimally differentiate and proliferate progenitor cells, growth factors (GFs) are required. Platelet rich fibrin (PRF) has many GFs and can be easily manufactured. Core-binding factor subunit-α1 (CBF-α1) constitutes a well-known osteogenic differentiation transcription factor in SPCs. Sox9, as a chondrogenic transcription factor, interacts and inhibits CBF-α1, but its precise role in direct in vitro osteogenesis remains unknown. GSPCs cultured in vitro in PRF to optimally stimulate osteogenic differentiation has been largely overlooked. The aim of this study was to analyze GSPCs cultured in PRF osteogenic differentiation predicted by CBF-α1/Sox9. Methods : This study used a true experimental with post-test only control group design and random sampling. GPSCs isolated from the lower gingiva of four healthy, 250-gram, 1-month old, male Wistar rats ( Rattus Novergicus ) were cultured for two weeks, passaged every 4-5 days. GSPCs in passage 3-5 were cultured in five M24 plates (N=108; n=6/group) for Day 7, Day 14, and Day 21 in three different mediums (control negative group: αModified Eagle Medium; control positive group: High Glucose-Dulbecco’s Modified Eagle Medium (DMEM-HG) + osteogenic medium; Treatment group: DMEM-HG + osteogenic medium + PRF). CBF-α1 and Sox9 were examined with ICC monoclonal antibody. A one-way ANOVA continued with Tukey HSD test (p<0.05) based on Kolmogorov–Smirnov and Levene's tests (p>0.05) was performed. Results: The treatment group showed the highest CBF-α1/Sox9 ratio (16.00±3.000/14.33±2.517) on Day 7, while the lowest CBF-α1/Sox9 ratio (3.33±1.528/3.67±1.155) occurred in the control negative group on Day 21, with significant difference between the groups (p<0.05). Conclusion: GSPCs cultured in PRF had potential osteogenic differentiation ability predicted by the CBF-α1/sox9 ratio.